(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The role of women in Rastrakuta society and politics, spanning from the 8th to the 10th centuries CE, was multifaceted and influential despite the overarching patriarchal constraints of the time. Women in the Rastrakuta dynasty exerted significant influence through strategic marriages, familial connections, religious and cultural patronage, and economic activities. Royal women, such as queens and princesses, were pivotal in forming dynastic alliances through marriage, which served as political tools to secure loyalty and peace among neighboring states. They often acted as advisors and regents, exercising substantial behind-the-scenes political power, and played crucial roles in mediating conflicts and maintaining stability within the royal court.